2020
DOI: 10.21203/rs.3.rs-34150/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative study on indoor air quality variation while burning different firewood species in Gatlang, Rasuwa, Nepal

Abstract: Indoor Air Pollution (IAP) from smoky cooking fires causes deaths over 22,800 per year being the fourth leading cause of death in Nepal. The study aims to compare the pollution level particularly Carbon Monoxide (CO) and Particulate Matter (PM 2.5 ) in different firewood species. Two households one with ICS and TCS is selected purposively to monitor the concentration of pollutants in Ward no. 3 of Gatlang, Rasuwa, Nepal. IAP Meter based on Laser Sensor principle is used to monitor real time concentration of PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Residual variation in cooking exposures, possibly related to firewood type or moisture content, type of food cooked, or daily weather conditions, was unexplained by the current models. Observations in the village suggested a role for these factors in influencing cooking related PM 2.5 concentrations, in keeping with evidence from other studies 50 52 , but difficulties in quantification and sample size limitations precluded their incorporation in the analysis.…”
Section: Discussionsupporting
confidence: 79%
“…Residual variation in cooking exposures, possibly related to firewood type or moisture content, type of food cooked, or daily weather conditions, was unexplained by the current models. Observations in the village suggested a role for these factors in influencing cooking related PM 2.5 concentrations, in keeping with evidence from other studies 50 52 , but difficulties in quantification and sample size limitations precluded their incorporation in the analysis.…”
Section: Discussionsupporting
confidence: 79%
“…Indoor air pollution poses a significant health risk. Incidences were prevalent among people in the Gasa district (91.5%), followed by Haa (89%) and Bumthang (87%), who are also highlanders, as recorded, 7 and 40% of the households in Thimphu still use firewood 8 . To further evaluate indoor pollution, the combustion by-products of widely used kerosene stoves, heaters, and lamps, aside from firewood alone, were found to be inevitable in the rural community of Bhutan.…”
Section: Introductionmentioning
confidence: 86%
“…6 The Population and Housing Census showed that the proportion of households using firewood for cooking in rural areas decreased from 56.6% in 2005 to 36.7% in 2017. 7 Although 99% of households in Bhutan have access to electricity, 33.3% of rural households currently use firewood as an energy source. Solid fuels, such as different types of firewood and other related biofuels, are mostly combusted in inefficient traditional mud stoves without smoke venting systems.…”
Section: Introductionmentioning
confidence: 99%